Diversity and utilization of ethnomedicinal plants in Sarawak, Borneo - Abu Bakar, Fauziah; Khan, Waseem Razzaq; Khan, Ishfaq Ahmad; Magiman, Mohamad Maulana; Rosli, Zamri; Seemab, Akram; I., Faridah-Hanum (Forestry Department Peninsular Malaysia, 2022)
Using medicinal plants for various treatments has been practiced for centuries. This traditional medicinal knowledge has been passed orally from generation to generation. Today's generation does not take much interest, and there is a threat of extinction of therapeutic expertise, thus it needs to be documented. For this purpose, a review was conducted to investigate the diversity of therapeutic plants and their utilization for different treatments among the local ethnic groups of Sarawak, Malaysia. Information regarding medicinal plants and their utilization was extracted from published articles, books, and thesis using various databases such as Google scholar, Scopus, and web of Science. A total of 166 therapeutic plants were utilized by native communities of Sarawak, where most of the plant species were used to treat gastrointestinal disorders and cardiovascular illnesses. Most plant species used for medicinal purposes belong to Rubiaceae, Piperaceae, Leguminosae, Lamiaceae, Annonaceae, and Zingiberaceae. As per our findings, the decoction was the most frequent way of medicine preparation, and leaves were the most frequent plant component used for medicine. The preference for leaves over other plant parts may be sustainable and encouraging in the current climate and biodiversity crisis.